Bilateral tarsal coalition in a National Collegiate Athletic Association Division I basketball player: a case report - Suits, J. M.; Oliver, G. D. (Journal of Athletic Training, 2012)
Objective: To present a case of bilateral subtalar joint coalition in a National Collegiate Athletic Association Division I basketball player and the treatment plan that was used to manage the coalition from the beginning of conference play through the postseason. Background: A 20-year-old male basketball athlete (height = 182.8 cm, mass = 83.4 kg) presented with bilateral subtalar joint tarsal coalition that became symptomatic in 2006 and resulted in constant pain with any form of activity. Differential Diagnosis: Traumatic injury of the talocalcaneal joint. Treatment: Nonsurgical intervention of conservative therapy was elected. Uniqueness: Less than 13% of the overall population is affected with tarsal coalition, so it is safe to assume that very few athletes competing at the collegiate or elite level suffer from this condition. This is the first report in the literature to document conservative manual therapies used to manage the symptoms of subtalar joint tarsal coalition in a Division I basketball player. Conclusions: After the intensive treatment program for tarsal coalition was implemented, the patient experienced pain relief and was able to continue to compete at a competitive level. This case represents the need to further explore and document a conservative treatment protocol for tarsal coalition.